Analisis Ventilasi Alamiah Pada Greenhouse Tipe Standard Peak Menggunakan Computational Fluid Dynamics: Natural Ventilation Analysis of Standard Peak Greenhouse using ComputationalFluid Dynamics - Yayu Romdhonah; Herry Suhardiyanto; Erizal Erizal; Satyanto Krido Saptomo (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2015)
Standard peak greenhouse is an adapted design for the humid tropical regions. Analysis of the greenhouse natural ventilation had been conducted using 3D Computational Fluid Dynamics (CFD). The objective of this research was to investigate the greenhouse natural ventilation performance on zero and low windspeed conditions. SolidworksÂ® CFD software was used in this study. Climate data and greenhouse characteristics were used as inputs for the simulation. The results of CFD simulation were presented in 3D of airflow vectors in x, y, and z directions. Results of this study showed the importance of roof vents and sidewalls openings for efficient thermally driven ventilation.